2021
DOI: 10.11113/sh.v13n2.1723
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Readiness and Use of Flipped Classroom among Education Geography Student / Pengetahuan, Kesediaan dan Penggunaan Flipped Classroom Dalam Kalangan Pelajar Pendidikan Geografi UPSI

Abstract: This study aimed to identify the learning methods based on the flipped classroom model among UPSI’s Geography students, focusing on the students who have completed university education courses including the courses that implement flipped classroom in line with the 21st Century Approach. A quantitative approach was applied in this study using a questionnaire as a research instrument. The study respondents included 92 samples from a total population of 120 students selected through simple random sampling. The qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
2
0
2
Order By: Relevance
“…Readiness refers to teachers' and students' willingness and ability to use the flipped classroom. Previous research on future geography teachers found a high positive correlation between readiness and actual implementation (Mahat et al, 2021). A correlation has also been observed between student and teacher readiness; students are more likely to be prepared when their teachers are (Kazu & Yalcin, 2022).…”
Section: Readiness For Flipped Classroommentioning
confidence: 90%
“…Readiness refers to teachers' and students' willingness and ability to use the flipped classroom. Previous research on future geography teachers found a high positive correlation between readiness and actual implementation (Mahat et al, 2021). A correlation has also been observed between student and teacher readiness; students are more likely to be prepared when their teachers are (Kazu & Yalcin, 2022).…”
Section: Readiness For Flipped Classroommentioning
confidence: 90%
“…Similarly, Suryawan et al (2021) found that implementing this learning approach also contributed to an enhancement in students' mastery level. In addition, previous research on students' readiness to follow flipped learning found that students are indeed ready to participate in flipped learning (Jiang et al, 2021;Mahat et al 2021;Tomas et al, 2019).…”
Section: Google Applicationmentioning
confidence: 97%
“…dalam kelas yang diikuti. Mahat et al (2021) telah menjalankan kajian yang melibatkan pelajar Geografi semester 7 Universiti Pendidikan Sultan Idris, UPSI untuk mengenal pasti tahap pengetahuan, kesediaan dan penggunaan flipped classroom dalam kalangan pelajar. Kaedah pembelajaran Flipped classroom di UPSI digunakan untuk membantu guru dan juga pelajar mempelbagaikan aktiviti melalui akses bahan-bahan pembelajaran seperti nota di laman web, video, kuiz online dan banyak lagi untuk pembelajaran dalam talian.…”
Section: Kajian Berkaitan Pembelajaran Dalam Talian DI Sekolahunclassified
“…Berdasarkan analisis ini, min skor yang paling tinggi adalah pada item 4 iaitu pelajar sedar bahawa Google Classroom merupakan aplikasi yang digunakan untuk pembelajaran dan mempunyai banyak kelebihan. Hasil kajian ini selari dengan kajian Mahat et al (2021) yang menegaskan dalam kalangan pelajar Geografi di Universiti Pendidikan Sultan Idris, penggunaan teknologi seperti nota dalam talian yang digunakan oleh pelajar untuk pembelajaran di rumah merupakan satu norma bagi pelajar semasa pembelajaran secara maya. Chen (2016) juga menyatakan dalam pendekatan pedagogi baharu ini, pelajar perlu menjana pengetahuan baru khususnya dalam bidang teknologi bukan sahaja perlu memahami kandungan mata pelajaran.…”
Section: Perbincangan Dapatan Kajianunclassified